Cycle Model Of Integrative-Interconnective Strategy within Character Learning - Anam, Nurul; Degeng, I Nyoman Sudana; Kuswandi, Dedi; Sulton (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2024)
Received: Revised: Accepted: This paper describes the cycle model of integrative-interactive character learning strategies at ‘MTs’ (Islamic Junior High School) Islamic Boarding School. The data is focused on MTs Al-Qodiri 1 and Nuris 1 Jember. This study used a qualitative approach having a multi-site research principle. The findings of this study showed that the application of the cycle model of integrative-interactive character learning strategies in MTs Islamic Boarding School has its own characteristics and can be considered to be a successful model of student character development. Character learning materials, especially the character values are the integration of values within the formal curriculum and Sufi based Islamic Boarding School typical curriculum. The materials are organized through the process of determining the material, structuring the order, constructing analogy, and summarizing the contents of character learning. Various interactive, collaborative and learning media are used, so that the transfer process of character learning material is easily understood and practiced in daily life. In order to ensure that the organization and the process of learning provision are more optimal, the character learning regulation is carried out by a 24-hour scheduling process followed by a continuous process of monitoring, motivational management, and supervision.